2005
DOI: 10.1080/08035250510025879
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of coeliac disease as detected by screening in children with iron deficiency anaemia

Abstract: The prevalence of coeliac disease was high in patients with iron deficiency anaemia; therefore, gastrointestinal findings should be further examined for coeliac disease, and the possibility of coeliac disease should be investigated in patients with recurrent iron deficiency anaemia and short stature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
2
24
0
2
Order By: Relevance
“…[7] CD is characterized by symptoms of malabsorption such as weight loss, diarrhea, steatorrhea, or abdominal distension. But CD may present with a broad spectrum of clinical features such as isolated iron defi ciency anemia, [8][9][10] short stature, [11] osteoporosis, [12] neurological disease, [13] non-specifi c abdominal symptoms or any associated disorders including autoimmune thyroiditis [14,15] and IDDM. [16] Growth failure is one of the well known manifestations of overt CD.…”
Section: Discussionmentioning
confidence: 99%
“…[7] CD is characterized by symptoms of malabsorption such as weight loss, diarrhea, steatorrhea, or abdominal distension. But CD may present with a broad spectrum of clinical features such as isolated iron defi ciency anemia, [8][9][10] short stature, [11] osteoporosis, [12] neurological disease, [13] non-specifi c abdominal symptoms or any associated disorders including autoimmune thyroiditis [14,15] and IDDM. [16] Growth failure is one of the well known manifestations of overt CD.…”
Section: Discussionmentioning
confidence: 99%
“…Of those 4.4%, 66.7% on retrospective questioning had occasional foul smelling or watery stool attacks, 66.7% had recurrent IDA and 50% had short stature 1. This compares with another smaller study of 25 patients which found that 44% of IDA patients had CD 3.…”
Section: Commentarymentioning
confidence: 75%
“…The weakness of this evidence is that only two studies1 3 looked prospectively at screening for CD in patients presenting with IDA and only one had a control arm 1. The other studies have gathered data retrospectively, with results varying partially due to inconsistent criteria used to select patients and reporting criteria.…”
Section: Commentarymentioning
confidence: 99%
“…Hastamızın komplike febril konvülziyonu da olması nedeniyle demir tedavisi glutensiz diyet ile eşzamanlı olarak başlandı. Demir eksikliği anemisi olan çocuk-larda ise ÇH sıklığı % 4.4 olarak bildirilmiştir 11 . Kieslich ve ark.…”
Section: Sonuçunclassified